Legal Anthropology Perspective on Restorative Justice in Indonesian Correctional Institutions: Harmonizing State Law and Local Cultural Values - Muhammad Fadli (Punggawa Global Research: Jurnal Multidisiplin, 2026)
and social institutions in shaping human behavior. In Indonesia, the implementation of restorative justice has increasingly become an important approach within correctional institutions to promote rehabilitation rather than punishment. This study aims to analyze restorative justice from the perspective of legal anthropology by exploring how formal legal norms interact with local cultural values in Indonesian correctional institutions. The research employed a qualitative literaturereview using academic journal articles, books, legislation, and policy documents related to legal anthropology and restorative justice. The findings indicated that restorative justice reflects the integration of state law and customary values emphasizing reconciliation, social harmony, and community participation. Cultural traditions such as deliberation, consensus-building, and collective responsibility strengthen correctional programs designed to facilitate offender reintegration into society. Nevertheless, challenges remain due to differences in legal culture, institutional capacity, and inconsistent implementation across correctional facilities. This study concludes that legal anthropology provides a comprehensive framework for understanding restorative justice as a culturally responsive legal practice that promotes social justice, rehabilitation, and sustainable conflict resolution in Indonesia.